The Challenge of Technical and Vocational Training and Education in Rural Areas: the Case of South-Asia - Vollmann, Wolfgang (Journal of Education and Research, 2010)
Although TVET appears as a viable alternative to general secondary education, available enrolment data in the South Asia show that formal TVET does not attract enough students yet. The lack of political support seems to be based on political considerations by local politicians inclined to follow mainstream thinking and attitudes, avoiding to antagonize their political support groups or voter banks. It may be said, that promoting TVET would currently require a considerable political courage, defying the odds, and going against popular thinking and expectations. This papers highlights the status of TEVT with data and concludes that current TVET policies are not meeting the identified challenges in the rural areas of South-Asia. DOI: http://dx.doi.org/10.3126/jer.v2i0.7623 Journal of Education and Research Vol. 2, 2010 p.52-58